Endogenous Annexin-A1 Negatively Regulates Mast Cell-Mediated Allergic Reactions - Sinniah, Ajantha; Yazid, Samia; Bena, Stefania; Oliani, Sonia M.; Perretti, Mauro; Flower, Rod J. (Frontiers Media, 2019)
Mast cell stabilizers like cromoglycate and nedocromil are mainstream treatments for ocular allergy. Biochemical studies in vitro suggest that these drugs prevent mast cell degranulation through the release of Annexin-A1 (Anx-A1) protein. However, the direct effect of Anx-A1 gene deletion on mast cell function in vitro and in vivo is yet to be fully investigated. Hence, we aim to elucidate the role of Anx-A1 in mast cell function, both in vivo and in vitro, using a transgenic mouse model where the Anx-A1 gene has been deleted. Bone marrow-derived mast cells (BMDMCs) were cultured from wild-type animals and compared throughout their development to BMDMCs obtained from mice lacking the Anx-A1 gene. The mast cell differentiation, maturity, mediator, and cytokine release were explored using multiple biochemical techniques, such as Western blots, ELISA, and flow cytometry analysis. Electron microscopy was used to identify metachromatic granules content of cells. For in vivo studies, Balb/C wild-type and Anx-A1-deficient mice were divided into the following groups: group 1, a control receiving only saline, and group 2, which had been sensitized by prior exposure to short ragweed (SRW) pollen by topical contact with the conjunctival mucosae. Allergic conjunctivitis was evaluated blind after 24 h by trained observers scoring clinical signs. Electron micrographs of BMDMCs from Anx-A1-null mice revealed more vacuoles overall and more fused vacuoles than wild-type cells, suggesting enhanced secretory activity. Congruent with these observations, BMDMCs lacking the Anx-A1 gene released significantly increased amounts of histamine both spontaneously as well as in response to Ig-E-FcεRI cross-linking compared to those from wild-type mice. Interestingly, the spontaneous release of IL-5, IL-6, IL-9, and monocyte chemoattractant protein-1 (MCP-1) were also markedly increased with a greater production observed upon IgE cross-linking. This latter finding is congruent with augmented calcium mobilization in BMDMCs lacking the Anx-A1 gene. In vivo, when compared to wild-type animals, Anx-A1-deficient mice exposed to SRW pollen displayed exacerbated signs and symptoms of allergic conjunctivitis. Taken together, these results suggest Anx-A1 is an important non-redundant regulator of mast cell reactivity and particularly in allergen mediated allergic reactions. © 2019 Sinniah, Yazid, Bena, Oliani, Perretti and Flower. This is an open-access article distributed under the terms of the Creative Commons Attribution License (CC BY). The use, distribution or reproduction in other forums is permitted, provided the original author(s) and the copyright owner(s) are credited and that the original publication in this journal is cited, in accordance with accepted academic practice. No use, distribution or reproduction is permitted which does not comply with these terms.